2013
DOI: 10.4236/oji.2013.34027
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal modulation of the C-type lectin MGL on human DCs

Abstract: The C-type lectin MGL is a pathogen recognition receptor, expressed by dendritic cells (DCs) and macrophages (Ms), able to bind GalNAc (Tn)-carrying structures. This receptor also recognized Tn-TAAs that were internalized, processed and presented by DCs to T cells and it acted as an adjuvant on DCs, highlighting its possible application in anti-cancer vaccination. In this work, we found that this receptor present a seasonal modulation: its expression is higher in winter rather than in summer. The percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In humans, monocyte-derived DCs express moderate MGL levels, which become negative after DC maturation. In addition variation of its expression related to seasonal changes is observed [ 42 ]. Moreover, MGL is upregulated on tolerogenic DCs generated in the presence of glucocorticoids and during chronic inflammatory conditions such as rheumatoid arthritis, implicating MGL in immune regulation [ 43 ].…”
Section: Human Mgl In Immune Responsementioning
confidence: 99%
“…In humans, monocyte-derived DCs express moderate MGL levels, which become negative after DC maturation. In addition variation of its expression related to seasonal changes is observed [ 42 ]. Moreover, MGL is upregulated on tolerogenic DCs generated in the presence of glucocorticoids and during chronic inflammatory conditions such as rheumatoid arthritis, implicating MGL in immune regulation [ 43 ].…”
Section: Human Mgl In Immune Responsementioning
confidence: 99%
“…MGL is most highly expressed on immature DCs (iDCs), monocyte-derived DCs (moDCs), CD1c+ DCs as their specific marker, and alternatively activated macrophages (subtype M2a), and its level may depend on various factors and the local microenvironment [14,[35][36][37][38][39]. Zizzari et al [39] found that the variation in MGL expression depends on seasonal changes with a negative trend that dropped to 33% during the summer and increased to 100% in winter. In turn, van Vliet et al [25] observed MGL upregulation on tolerogenic DCs in the presence of immunosuppressive dexamethasone and during chronic inflammatory conditions such as rheumatoid arthritis.…”
Section: Mgl As a Guardian Of Immune Homeostasismentioning
confidence: 99%